DAYA TAHAN PARTAI GOLKAR PROVINSI BALI (STUDI KEPENGURUSAN GANDA TAHUN 2014-2015) - Indrawati, Ni Putu Ayu; Ali Azhar, Muhammad; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2019)
ABSTRACTU TheP success of Golkar in overcoming multiple management conflicts in 2014-2015 had an impact on the management of the Bali Province. This makes Golkar seen as a strong political party in the institutional system, infrastructure, and internal party mechanisms. This strength is the main attraction of the writer to analyze it with the theory of Talcott Parson Functionalism with the concept of the scheme A-G-I-LP (Adaptation,pGoal Attainment, eIntegration, land pLatency). This study uses a qualitativei descriptiveo approachi. Thep resultsi of thei studyp indicate that Golkar's success in defending itself from the shocks of party internal conflicts stemmed from the Party's strength. According to the theory used the results of the study showi thati first, thei adaptation scheme, used by Golkar as a form of the main force in maintaining existential and determining the direction of the Golkar party in the new political era. Second, the goal attainment scheme shows that Golkar's strength is based on an ideological foundation, intellectual strength, and work-oriented orientation. Butu on thei otherp handi, the strong leadership in the Golkar party plays a very important role as a driver of cadre consolidation in maintaining the existence of the party in the community. Third, Golkar in maintaining party resistance also prioritizes the consistency of cadres in framing a good party platform as its Integrity. And fourth, Golkar in identifying itself as an open, moderate and democratic party, so in the framework of safeguarding this, the Golkar Party continues to maintain the Pancasila ideology as the latency that underlies each of its actions and maintains its old brand, which is Golkar. Keyword: Golkar, Scheme (A-G-I-L) Golkar Party and Double Management.